Investigating the Adipogenic Effects of Different Tissue-Derived Decellularized Matrices - Tang, Weiya; Qi, Jun; Wang, Qian; Qu, Yaping; Fu, Su; Luan, Jie (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: Decellularized adipose-derived matrix (DAM) can promote adipogenic differentiation and adipose tissue remodeling, but the biological impact of tissue origin on DAM remains unknown. The present study aimed to investigate the effects of tissue origins on the adipogenic capacity of the decellularized matrix by comparing the cellular and tissue responses of DAM versus acellular dermal matrix (ADM). Methods: The in vitro response of adipose-derived stem/stromal cells (ADSCs) to DAM and ADM was characterized by proliferation and differentiation. The in vivo remodeling response was evaluated in the subcutaneous injection model of immunocompromised mice, using histology, protein expression, and transcriptome analysis. Results: Both DAM and ADM exhibited excellent decellularization effects and cytocompatibility. In the absence of exogenous stimuli, DAM could induce adipogenic differentiation of ADSCs compared with ADM. In the animal model, the levels of PDGF, VEGF, and ACRP30 were higher in the DAM groups than in the ADM group, and more neovascularization and extensive adipose tissue remodeling were observed. The mRNA-seq analysis indicated that the DAM implant regulated tissue remodeling by modulating Lat1/2 expression along with Hippo Signaling pathway in the early stage. Conclusion: Tissue origin can influence the biological response of the decellularized matrix. DAM can retain favorable tissue-specific characteristics after the decellularization process and have unique adipogenic effects in vitro and vivo, which can be fully utilized for soft tissue repair and regeneration.